INTERNATIONAL CRIMINAL LAW - Branko Sekuloski (European Scientific Journal, ESJ, 2013)
This paper contains the concept and development of International criminal law. Regarding with concept there are given several opinions of several eminent world authors. Given is a author opinion of the paper about the concept of International criminal low. Further in the paper is described the development of International criminal law. The development of the International criminal law covers the period of all social formations. At the end of the paper, given is the opinion of the author, according to which in XXI century International criminal law as a universal and over international will experience expansion in its development.